Seasoned equity issuers' prospectus filings: How informative is their tone?. Issue 2 (24th February 2022) - Huang, Rongbing; Qian, Hong; Ramalingegowda, Santhosh
Abstract: Seasoned equity issuers file Forms S and 424B with the Securities and Exchange Commission. We find that 424B filings' weak‐modal tone is positively related to offer price discounts and negatively related to offer‐day stock returns. Increases in cautionary (weak‐modal, uncertain, and negative) tone from the initial to final filing are followed by lower abnormal stock returns. Preliminary evidence indicates that cautionary tone relates positively to litigation risk and increased after the passage of the Sarbanes‐Oxley Act. Our findings suggest that the cautionary tone of seasoned equity issuers' prospectuses has negative information content, which is gradually incorporated into the stock prices.